2023
DOI: 10.3390/stresses3020033
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hormones and the Potential Impact of Multiple Stresses on Infertility

Shanmugam Ramya,
Prasad Poornima,
Arumugam Jananisri
et al.

Abstract: Infertility has a remarkable global impact affecting approximately about 48 million couples worldwide. One of the most contended concerns in reproductive biology is the prospective influence of psychological stress on pregnancy rates. Individuals struggling to conceive face a stupendous amount of emotional turbulence and have a greater risk for psychological vulnerability. Both stress and infertility reinforce the impact of each other; hence, there exists a reciprocal relationship. Stress may be the major cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 164 publications
0
6
0
Order By: Relevance
“…Conversely, another investigation projected the prevalence of diagnosed homocystinuria in the US to span between 12,113 and 31,162 cases [5]. In an observational cross-sectional study focusing on an elderly demographic, while the prevalence of total hyperhomocysteinemia was not explicitly disclosed, the findings underscored a significant age-related increase in homocysteine levels [41].…”
Section: Prevalence Of Elevated Homocysteinementioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, another investigation projected the prevalence of diagnosed homocystinuria in the US to span between 12,113 and 31,162 cases [5]. In an observational cross-sectional study focusing on an elderly demographic, while the prevalence of total hyperhomocysteinemia was not explicitly disclosed, the findings underscored a significant age-related increase in homocysteine levels [41].…”
Section: Prevalence Of Elevated Homocysteinementioning
confidence: 99%
“…While advances in assisted reproductive technologies have provided hope and options for many subfertile couples, much remains unknown about the underlying causes of subfertility. This knowledge gap underscores the need for comprehensive research into the factors contributing to subfertility [3][4][5]. In recent years, emerging evidence has suggested a potential link between elevated serum homocysteine levels and subfertility.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been noted that some women with PCOS have reduced antioxidant defense mechanisms, which can lead to an imbalance between ROS production and antioxidant defense, resulting in increased OS [ 24 , 25 ]. In addition, an imbalance in luteinizing hormone (LH), follicle-stimulating hormone (FSH), and other reproductive hormones can affect ovarian function and may contribute to ROS production [ 26 ].…”
Section: Ros Productionmentioning
confidence: 99%
“…However, testosterone’s role in OS is controversial. Multiple studies have demonstrated that testosterone induces OS in the muscle, testis, and human placenta ( 76 ); others indicate that testosterone has antioxidant properties in the prostate and nervous tissue ( 77 ). Testosterone supplements improve the OS parameters in brain tissues and raise antioxidant enzyme levels to reduce oxidative damage.…”
Section: Adrenal Hormonal Imbalance-associated Oxidative Stressmentioning
confidence: 99%